The Impact Organizational Culture, Employment Spirit And, Job Satisfaction On Employee Work Productivity - Sinta Veronika Hutabarat (Institute of Computer Science (IOCS), 2021)
The definition of the issue in this examination is whether hierarchical culture, work excitement, and occupation fulfillment have a concurrent beneficial outcome on representative work efficiency at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City. This investigation means to decide the impact of the impact of hierarchical culture, work soul, and occupation fulfillment on the work usefulness of representatives at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City. The example in this examination were all workers at the Village Community Empowerment Service, Women's Empowerment and Child Protection in Sibolga City, upwards of 42 individuals. The information investigation method in this assessment is Multiple Linear Regression Analysis.The outcomes showed; Organizational Culture part of the way has no impact and isn't huge on Employee Performance; Work spirit halfway has a positive and critical impact on Employee Productivity; Job fulfillment in part immensely affects delegate productivity